Stress and Covid-19: Physical Education Students' Stress Levels in Completing Final Projects - Oki Candra; Zulrafli; Ahmad Rahmadani; Daharis (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study was intended to determine the extent of student stress in completing the final project of the physical education and recreation study program, Islamic University of Riau. This study adopted a quantitative descriptive approach. The population and sample of the study were students of physical education, health, and recreation, the Islamic University of Riau in the final semester consisting of 63 people. Sampling was done by using random sampling. The procedure in the study consisted of preparing a questionnaire, validating the questionnaire, testing the questionnaire to be later validated and used as a research tool for the intended sample. Based on the results of data processing and data analysis that has been carried out, it was concluded that the symptoms of stress for final-year students of physical education, health, and recreation, Islamic University of Riau during the Covid-19 pandemic had an average of 40% and included in the mild category. Academically, based on the results of research that aims to see how far the stress level of students in completing studies during the Covid-19 pandemic, it is necessary to carry out an evaluation to overcome existing problems, both from supervisors and students themselves.